The Effect of NPL, BI Rate, Inflation, LDR and Company Size on Profitability - Sutrisno , Sutrisno; Santoso, R Eri Wibowo Agung; Kristiana, Ida (Economics and Business International Conference Proceeding, 2024)
This study aims to examine the influence of non-performing loans (NPL), BI rate, Inflation, loan deposit to rate (LDR), and company size on profitability. This type of research is quantitative research. The sample in this study was obtained using the purposive sampling method, which is the selection of samples with predetermined criteria. Based on the purposive sampling method, 236 samples were obtained from 49 conventional commercial banks registered with the OJK from 2019 to 2022. The analysis technique used is multiple linear regression. The results of the data analysis showed that the hypothesis testing of partial non-performing loans (NPLs) had a negative effect on profitability, the BI rate had a positive effect on profitability, inflation had no effect on profitability, the loan to deposit rate (LDR) had a positive effect on profitability, and the size of the company had a positive effect on profitability. Simultaneously, NPL, BI rate, inflation, LDR, and company size have a positive effect on profitability.